Micro-patterned plasma polymer films for bio-sensing. (15th January 2017) - Vandenbossche, Marianne; Bernard, Laetitia; Rupper, Patrick; Maniura-Weber, Katharina; Heuberger, Manfred; Faccio, Greta; Hegemann, Dirk
Abstract: Bi-functional micro-patterned plasma polymer films were prepared by first depositing a full-area amino-containing plasma polymer film (PPF) onto a substrate, followed by the deposition of a patterned oxygen-containing PPF via a polymeric mesh used as contact mask. As a result, an ultrathin film with alternating areas of amine and oxygen-containing groups is obtained. Such micro-patterns bear potential as templates for multi-sensitive bio-sensor substrates. The chemical surface composition is assessed using XPS and ToF-SIMS. On the masked amino-rich area a lateral chemical micro gradient was observed due to mesh mask shadowing. Stability of the coating was investigated over time in ambient air and in water, showing that the surface properties were maintained after 7 days in air and 1 day in water. To demonstrate functionality, the micro-patterned surface was exposed to a green fluorescent protein (GFP) and lateral resolution and selectivity during adsorption was studied. Graphical abstract: Highlights: Deposition of a micro-patterned plasma polymer film using a polymeric mesh mask Well-defined deposition of oxygen-containing groups and amino groups in the coating Formation of a vertical and lateral chemical gradients while preparing the film Adsorption of fluorescent protein GFP enhanced on nitrogen-containing area